Morphological changes and expression of protein markers during remodeling of tissue-engeneered skin - Mohd Monzai, Norhayati (2009)
The studied was carried out to evaluate the skin remodeling and skin development after bilayered fibrin – fibroblast / fibrin – keratinocytes skin equivalent (B FF/FK SE) and fibrin without seeded cell (FWC) were transplanted into eight weeks old athymic mice. During skin remodeling, the structural, ultrastructural features and protein expression were investigated. The keratinocytes and fibroblasts were isolated and cultured until propagated. The B FF/ FK SE was produced by incorporated the karetinocytes and fibroblasts with human fibrin. Then, constructed skin was harvested after 1, 7, and 14 days in vitro and 30 and 60 days in vivo for electron microscopy analysis and immunolabelling. Grossly, the wound margin transplanted with B FF/ FK SE appeared constantly pink whereas with FWC, necrotic zone appeared yellowish. Light microscopy revealed that B FF/ FK SE has good skin remodeling capacity with 6-12 cells thick after 60 days post-transplantation whereas FWC was only 3-4 cells thick. The mean number of keratinocytes and fibroblast was pursued by using Duncan test and one way ANOVA which showed that B FF/FK SE was capable for generating the dermal-epidermal layer in shorter period of time compared to FWC (p ≤ 0.05). Further studies were done using the structural features of B FF/FK SE and FWC in vitro and in vivo. Scanning electron microscopy (SEM) revealed that keratinocytes and fibroblasts in B FF/ FK SE showed an excellent adherence in fibrin matrix and changes in their morphology after 1 to 14 days in vitro. It ranges from rounded to elongated and stellate shape, whereas, for FWC, no cells were selected. Stratified layer with sloughed off stratum cornneum was seen developing after B FF/ FK SE and FWC were transplanted onto athymic mice. Transmission electron microscopy (TEM) showed that the ultrastructural features during epidermal differentiation and regeneration as well as basement membrane formation were well developed after B FF/ FK SE and FWC transplanted onto athymic mice. The presence of keratinocyte clusters which migrated superiorly and fibroblast clusters which migrated interiorly at fibrin matrix mimicked a bilayered skin tissues whereas in contrast FWC showed no cell migration. However, both B FF/FK SE and FWC after implication, showed the formation of columnar stratum basale, stratum spinosum, stratum granulosum with keratohyaline granule and stratum corneum suggesting epidermal differentiation and regeneration might have occurred. Development of basement membrane in B FF/ FK SE with cell junction components such as hemidesmosome, lamina lucid, lamina densa and anchoring fibril network was established which was similar to native human skin. Furthermore, dermal organization of B FF/ FK SE showed a similarity to native human skin which has a compact basket weave pattern arrangement of collagen bundles whereas FWC showed a loose arrangement. Confocal microscopy revealed that immunolabelling of desmoglein 3 and plakophilin 1 at stratified layer, type Iv collagen at dermal margin were present after 60 days B FF/ FK SE post-transplantation which was similar to native human skin. Contrast, such observation was not detected for FWC. In conclusion, the B FF/ FK SE showed the better skin regeneration similar to native human skin and required a shorter period of time during wound healing without any contraction.